School librarians coping with electronic environment - Lasić-Lazić, Jadranka (Array, 2009)
Paper focuses on abilities of librarians to adapt and respond to the constantly emerging changes influenced by the advancement of ICT. The authors emphasize the necessity of defining and promoting new concept and understanding of the school library in electronic environment. Traditional school library roles need to adapt and change to respond to the needs of new users growing up in the interactive and information overloaded environment. Many of the aspects of current school library tasks and roles originate from a print-based culture which is incongruent with the transient and hybrid nature of digital environments. These radically changing environments are posing different tasks on school librarians leading them to balance carefully between the traditional school environments, infrastructure, institutions hierarchy and with the various new needs of “ Google generation” users. Taking into account all the changes in the information environment authors emphasise the necessary improvements in education of school librarians.